The Effect of Using Gallery Tour Strategy Toward Students’ Reading Comprehension at SMP N 5 Tahan Putih (International Journal of Business and Information Technology, 2022)
This paper entitled “The Effect of Using Gallery Tour Strategy toward Students’ Reading Comprehension at SMP N 5 Tanah Putih”. The objectives of the research is to find out the significant effect of using gallery tour strategy on the students’ reading comprehension at the eighth grade students of SMP N 5 Tanah Putih. This research is an experimental research. The design of this research is quasi experimental design, which uses two groups. The population of this research is the whole students of eighth grade students of SMP N 5 Tanah Putih. There are three classes that consist of VIII.1, VIII.2, and VIII.3. The total population is 100 students. The classes chosen are VIII.1 as the experimental class and VIII.3 as the controlled class. Each class consists of 34 and 33 students so the total of the sample is 67 students. The result of the research is there is significance effect of using gallery tour strategy toward the students’ reading comprehension of the eighth grade students of SMP N 5 Tanah Putih. It is gotten because of t-test is bigger than t-table = 12.935 is bigger than 2.0315 in degree of significance 5%, it could be concluded that Ha3 is accepted. In other words, There is significant effect of pre-test and post-test mean scores of using gallery tour strategy in experimental group. It means that there is a significant effect between pre-test and post-test mean score on students’ reading comprehension of the eighth grade students of SMP N 5 Tanah Putih.